Promoter DNA recognition by the Enterococcus faecalis global regulator MafR - Moreno-Blanco, Ana; Pluta, Radoslaw; Espinosa, Manuel; Ruiz-Cruz, Sofía; Bravo, Alicia (Frontiers in Molecular Biosciences, 2023)
When Enterococcus faecalis is exposed to changing environmental conditions, the expression of many genes is regulated at the transcriptional level. We reported previously that the enterococcal MafR protein causes genome-wide changes in the transcriptome. Here we show that MafR activates directly the transcription of the OG1RF_10478 gene, which encodes a hypothetical protein of 111 amino acid residues. We have identified the P10478 promoter and demonstrated that MafR enhances the efficiency of this promoter by binding to a DNA site that contains the -35 element. Moreover, our analysis of the OG1RF_10478 protein AlphaFold model indicates high similarity to (i) structures of EIIB components of the bacterial phosphoenolpyruvate:carbohydrate phosphotransferase system, and (ii) structures of receiver domains that are found in response regulators of two-component signal transduction systems. However, unlike typical EIIB components, OG1RF_10478 lacks a Cys or His residue at the conserved phosphorylation site, and, unlike typical receiver domains, OG1RF_10478 lacks a conserved Asp residue at the position usually required for phosphorylation. Different from EIIB components and receiver domains, OG1RF_10478 contains an insertion between residues 10 and 30 that, according to ColabFold prediction, may serve as a dimerization interface. We propose that OG1RF_10478 could participate in regulatory functions by protein-protein interactions.